2016
DOI: 10.1038/srep39552
|View full text |Cite|
|
Sign up to set email alerts
|

Synergistic Effect of Atmospheric-pressure Plasma and TiO2 Photocatalysis on Inactivation of Escherichia coli Cells in Aqueous Media

Abstract: Atmospheric-pressure plasma and TiO2 photocatalysis have been widely investigated separately for the management and reduction of microorganisms in aqueous solutions. In this paper, the two methods were combined in order to achieve a more profound understanding of their interactions in disinfection of water contaminated by Escherichia coli. Under water discharges carried out by microplasma jet arrays can result in a rapid inactivation of E. coli cells. The inactivation efficiency is largely dependent on the fee… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
42
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(42 citation statements)
references
References 43 publications
0
42
0
Order By: Relevance
“…technology for a wide range of applications from environmental remediation, such as gas conversion [194,195] and pollutant destruction [196,197], to biological engineering [198,199] have shown impressive results. In this system, the heterogeneous interdependence between plasma and catalyst is quite complex, with plasma inducing physicochemical changes in the catalysts and vice versa, the catalyst modifying the electric field distribution and gaseous chemical composition [as presented in Figure 15(a)].…”
Section: Plasma-solid Systemmentioning
confidence: 99%
“…technology for a wide range of applications from environmental remediation, such as gas conversion [194,195] and pollutant destruction [196,197], to biological engineering [198,199] have shown impressive results. In this system, the heterogeneous interdependence between plasma and catalyst is quite complex, with plasma inducing physicochemical changes in the catalysts and vice versa, the catalyst modifying the electric field distribution and gaseous chemical composition [as presented in Figure 15(a)].…”
Section: Plasma-solid Systemmentioning
confidence: 99%
“…In addition, the enhancement of plasma efficacy can also be achieved via synergistic action of plasma-mediated inactivation and biologically active silver nanomaterials, where, in addition to direct formation of oxidative species, the high catalytic activity and stability of plasma enhance chemical reactivity. Zhou et al (2016) explored the synergistic effect of atmospheric pressure plasma and TiO 2 photocatalysis on inactivation of E. coli cells in aqueous media, and results indicated that the inactivation efficiency of TiO 2 photocatalytic-assisted plasma treatment was significantly enhanced and the required time to achieve 99.9% killing of E. coli cells was also shortened by threefold.…”
Section: Methods For Improving Plasma Efficiencymentioning
confidence: 99%
“…Zhou et al. () explored the synergistic effect of atmospheric pressure plasma and TiO 2 photocatalysis on inactivation of E. coli cells in aqueous media, and results indicated that the inactivation efficiency of TiO 2 photocatalytic‐assisted plasma treatment was significantly enhanced and the required time to achieve 99.9% killing of E. coli cells was also shortened by threefold.…”
Section: Fundamentals Of Nonthermal or Cold Plasmamentioning
confidence: 99%
“…Krause tested an aluminum oxide-coated, rotating drum electrode, with the solution flowing on its outer surface as a thin film ( Figure 3A), while Magureanu used a dielectric barrier discharges (DBD) unit with falling film ( Figure 3B) [26,27]. Some recent developments in plasma technology include combination of atmospheric pressure plasma and photocatalysts (e.g., TiO 2 ) for microorganisms control in aqueous solutions [28]. After flowing through the 1st reactor, water is stored in a side tank.…”
Section: Non-thermal Plasma Technologymentioning
confidence: 99%